2008
DOI: 10.1227/01.neu.0000316286.29995.4c
|View full text |Cite
|
Sign up to set email alerts
|

Pretargeting for the Implantation of Stimulation Electrodes Into the Subthalamic Nucleus

Abstract: Our findings show that the indirect targeting of the STN using coordinates based on radiological landmarks is more accurate than the direct targeting using anatomic visualization of the target structure. Regardless of the imaging procedure, electrophysiological mapping is required for optimal electrode placement, although in 20% of cases, the target determined by MRI falls out of the radius explored by electrophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As this also translates into heterogeneity of therapy outcomes in PD, e.g., in patients treated with DBS, recent studies aimed to stratify patients and therapy outcomes according to the underlying genetic trait. In this context, studies on monogenic forms of Parkin-or LRRK2-related forms of PD revealed positive outcomes for STN-DBS up to 8-year follow-up (Breit et al 2008;Schupbach et al 2007;Moro et al 2008). Moreover, a recent pilot study identified genetic markers in the PD-associated alpha-synuclein gene as a predictor for a positive therapy outcome in patients treated with STN-DBS (Weiss et al 2013;DGN 2014 in München, Germany, Abstract, http:// www.neurowoche2014.org/epaper-DGN2014/index.html#/ 148).…”
Section: Discussionmentioning
confidence: 99%
“…As this also translates into heterogeneity of therapy outcomes in PD, e.g., in patients treated with DBS, recent studies aimed to stratify patients and therapy outcomes according to the underlying genetic trait. In this context, studies on monogenic forms of Parkin-or LRRK2-related forms of PD revealed positive outcomes for STN-DBS up to 8-year follow-up (Breit et al 2008;Schupbach et al 2007;Moro et al 2008). Moreover, a recent pilot study identified genetic markers in the PD-associated alpha-synuclein gene as a predictor for a positive therapy outcome in patients treated with STN-DBS (Weiss et al 2013;DGN 2014 in München, Germany, Abstract, http:// www.neurowoche2014.org/epaper-DGN2014/index.html#/ 148).…”
Section: Discussionmentioning
confidence: 99%